EFFECT OF TYPE 2 DIABETES MELLITUS ON BRAIN METABOLITES BY USING PROTON MAGNETIC RESONANCE SPECTROSCOPY -A SYSTEMATIC REVIEW - RAJANI SANTHAKUMARI,; INDLA YOGANANDA REDDY,; ARCHANA R, (International Journal of Pharma and Bio Sciences, 2014)
Cerebral metabolism will be affected in T2DM either by chronic hyperglycemia or by chronic hypoxia. Proton magnetic resonance spectroscopy (1H-MRS) of the brain provides detailed information about the structure, dynamics, reaction state and chemical environment of molecules. It also measures the levels of brain metabolites such as myo-inositol (mI), N acetyl aspartate (NAA), creatine (Cr), choline (Cho), glutamate (Glu), glutamine (Gln) and gamma amino butyric acid (GABA). Several studies suggest that people with type 2 diabetes mellitus (T2DM) are at an increased risk of cognitive impairment in comparison with the general population. The altered metabolites may cause cognitive dysfunction in T2DM. This review article concludes that in T2DM, metabolite levels were altered in different regions of brain.